THE FUTURE OF ARTIFICIAL INTELLIGENCE - Oktayeva Diloram Alisher qizi; Kubbieva Mubina Muhammad qizi (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Abstract: This article examines the role of artificial intelligence (AI) in modern society and its future development. The study analyzes the benefits, risks, and ethical challenges of AI implementation across different sectors. Special attention is given to its impact on education, healthcare, economy, and the labor market. The research is based on analytical and comparative methods, using modern scientific sources and reports. The findings indicate that artificial intelligence has transformative potential, but its development requires strict ethical regulation, transparency, and responsible usage to prevent negative social consequences.